Wild Hogs - Lieberman, Todd.; Robbins, Brian, 1963-; Tollin, Michael; Buena Vista Home Entertainment (Firm); Tollin/Robbins Productions; Tollin/Robbins Productions; Touchstone Home Entertainment (Firm); Touchstone Pictures; Wild Hogs Productions (Burbank, CA : Touchstone Home Entertainment, 2007)
Four middle-aged men decide to take a motorcycle road trip from Cincinnati to the Pacific in order to get away from their lives which are leading them nowhere. These "Wild Hogs" tear up the road and eventually stop in New Mexico for a drink, not knowing that the bar belongs to the Del Fuegos, a mean biker gang. When the Del Fuegos steal a bike that belongs to the Wild Hogs, Woody, one of the Hogs decides to steal the bike back. Woody cuts the fuel pipes of the bikes and provokes an accident that explodes the bar, but he does not tell the truth to his friends. When they stop in the small town of Madrid without gas, Dudley falls in love with the waitress and owner of the local bar Maggie. The Del Fuegos pursue the Hogs and trap them in the town
Keywords: Bars (Drinking establishments) -- New Mexico -- Drama; Man-woman relationships -- New Mexico -- Drama; Motorcycle gangs -- New Mexico -- Drama; Motorcyclists -- United States -- Drama; New Mexico -- Drama